The 1990's financial crises in Nordic countries - Seppo Honkapohja (Bank of Finland, 2009)
The current financial crisis, which has lasted almost one and a half years, is the 19th such crisis in the post-war period in advanced economies. Recent literature classifies the Nordic crises in Norway, Sweden and Finland in late 1980's and early 1990 s among the Big Five crises that have happened before the current crisis, which is now of a global nature. This paper outlines the developments of the Nordic crises, reasons behind them and crisis management by the authorities. Relatively more emphasis is placed on the Finnish crisis, as it was the deepest one. The paper concludes by considering the lessons that can be drawn from the Nordic crises
URN:NBN:fi:bof-20140807103
Keywords: 330